(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Entrepreneurship is the dominant culture these days by the government, public, and private institutions. Small institutions are looking to collaborate with others to establish an Entrepreneurial Ecosystem. Thus, providing the facilities and resources for the students to become entrepreneurs. An Entrepreneurial Ecosystem can be defined as any collaboration established between a university, industry, or institution to enhance and strengthen the entrepreneurial culture. An Entrepreneurial Ecosystem allows startups to create, take risks, and interact successfully. Robust Ecosystems make startups to access the information and resources they require to be competitive. After identifying the importance of inculcating entrepreneurial culture into students, which cannot happen individually, many institutions have started collaborating with ecosystem elements that share knowledge and facilities to enhance entrepreneurship. This entrepreneurial ecosystem plays a vital role in creating and sustaining innovations and creativity in the Country. The concept of the ecosystem is growing rigorously in educational institutions in the country. All the educational institutions are giving a lot of importance to entrepreneurship. This study aims to understand the components of the ecosystem, trends in the evolution of the entrepreneurial ecosystem, and the consequences of the startup era in India.